The Effect of The Culinary Night Festival on The Development of Local Tourism Potential in Kiaracondong - Sayangbatti, Dilla Pratiyudha; Djohan, Muhammad Iqbal; Permatasari, Mustika (Stupa, 2020)
Culinary is a brand and promotion for a country. Every country has a particular characteristic which makes it different from other countries. There are several creativity and hand-made concoctions from various countries that are familiar in our society, such as dishes and wine from France, Sushi from Japan, Pizza from Italy, Kebab from Turkey, Ice Cream from America, Cane Bread from India, and various culinary from other countries that come together with the symbol of the country of origin. Not only the food, but also the culinary culture has entered and exchanged the realm of our traditional cultural traditions, such as French-style banquets or French dishes. France offers a lot of uniqueness to the world community.Likewise in Indonesia, every province or city has special food and snacks. This sudy aims to know the influence of the Culinary Night Festival on the Development of Local Tourism Potential based Traditional Snacks in Kiaracondong District. The research shows that the traditional cakes have a distinctive taste in Kiaracondong. It is made from natural ingredients that are still feasible and can be explored more to be used as one of the preservation of culture that attracts tourists.